Impact of TRIPS : intellectual property protection in developing countries. - BRONCKERS, Marco C.E.J. (1994)
Discusses the controversy surrounding the negotiations of the agreement on trade-related aspects of intellectual property rights (TRIPS) of the Uruguay Round. Developing countries felt that intellectual property gave them little, if any, benefit. Concludes that the protection of intellectual property is an experiment which developing countries have been persuaded to enter into through the link between the TRIPS agreement and trade concessions granted pursuant to other Uruguay Round agreements. One way in which developed countries can contribute to the success of this experiment is by liberally interpreting their obligation to provide technical and financial assistance to developing countries. The developing countries, can make their own contribution, and also enhance their claims for such assistance by encouraging private investment.